2020
DOI: 10.1080/26895269.2020.1841058
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy intentions and outcomes among transgender, nonbinary, and gender-expansive people assigned female or intersex at birth in the United States: Results from a national, quantitative survey

Abstract: Background: Transgender, nonbinary, and gender-expansive (TGE) people experience pregnancy. Quantitative data about pregnancy intentions and outcomes of TGE people are needed to identify patterns in pregnancy intentions and outcomes and to inform clinicians how best to provide gender-affirming and competent pregnancy care. Aims: We sought to collect data on pregnancy intentions and outcomes among TGE people assigned female or intersex at birth in the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Of course, it should be remembered that not just heterosexual people, or people whose psychological gender is the same as their biological sex, can plan to be and be pregnant. People who do not identify as women, or who are trans, nonbinary or otherwise gender diverse can also be pregnant [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, it should be remembered that not just heterosexual people, or people whose psychological gender is the same as their biological sex, can plan to be and be pregnant. People who do not identify as women, or who are trans, nonbinary or otherwise gender diverse can also be pregnant [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with previous use of GAHT underwent more cesarean deliveries compared to those without the prior intake of GAHT (36% [9/25] versus 19% [3/16], respectively), the difference was not statistically significant [ 10 ]. A subsequent cross-sectional study based on a quantitative survey is in line with the finding that only a minority (23%) of transgender individuals deliver by cesarean section, although prior GAHT is not taken into account [ 11 ]. Both studies lack the comparison of pregnancy outcomes between singleton and multiple pregnancies, as well as between spontaneously conceived gestations and those obtained through assisted reproductive techniques.…”
Section: Discussionmentioning
confidence: 74%
“…This includes transgender, non-binary and gender-diverse people who do not have a gender identity and gender modality (see box 1) congruent with their assigned sex at birth 2. A recent study of gender-diverse people assigned female or intersex at birth found that 12% had been pregnant and 11% desired future pregnancies 3. With younger generations being more likely to openly identify as Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, Asexual, Two-Spirit, or other sexually- and gender-diverse identities (LGBTQIA2+),4 5 the proportion of pregnant people who do not identify as cisgender women can be expected to increase.…”
Section: Introductionmentioning
confidence: 99%